3D concrete printing modelling of thin-walled structures. (May 2022) - Nguyen-Van, Vuong; Nguyen-Xuan, H.; Panda, Biranchi; Tran, Phuong
Abstract: Failures induced by either instability (elastic buckling) or green strength (plastic collapse) mechanisms have been commonly encountered in 3D concrete printed (3DCP) structures. In this work, a numerical model of the 3D concrete printing process is implemented to simulate these two failure mechanisms. Early-age mechanical properties of two printable mixes are used as input data for the simulation. The finite element (FE) modelling is then validated by comparison with 3DCP experiments of a hollow cylinder. The numerical analysis program can accurately predict the deformation and its failure modes during the 3D concrete printing process. Besides, the FE model is also used for validating a printed free thin wall. Further, sensitivity and parametric analyses are investigated to unveil the influence of printing process parameters, i.e., printing speed, extrusion width, and different mesh sizes on buildability.